Influence of groundwater conditions and co‐contaminants on sorption of perfluoroalkyl compounds on granular activated carbon. Issue 3 (20th June 2019) - Siriwardena, Dinusha P.; Crimi, Michelle; Holsen, Thomas M.; Bellona, Christopher; Divine, Craig; Dickenson, Eric
Abstract: Per and polyfluoroalkyl substances (PFAS) are emerging and persistent organic pollutants that have been detected in many environmental media, humans, and wildlife. A common method to effectively remove PFAS from water is adsorption by activated carbon. Preliminary sorption experiments were conducted using five characterized Calgon Corporation coal‐based granular activated carbon (GAC; F100, F200, F816, F300, and F400), one coconut‐based GAC (CBC‐OLC 12 × 30), and one Jacobi Corporation coal‐based GAC (Omni‐G 12 × 40). Sorption of four representative PFAS onto each GAC was measured to select the most favorable carbon sources. F400 and CBC were chosen based on their performance in preliminary PFAS sorption experiments and contrasting properties. Freundlich and Langmuir isotherm models were developed for perfluorooctanoic acid (PFOA) and perfluorooctanoic sulfonate (PFOS) at an initial concentration of 1 mg/L. Sorption capacities were determined for PFOA and PFOS individually and in the mixture. Individual compounds showed higher sorption than when present in the mixture for both PFOA and PFOS. PFOS showed higher sorption than PFOA both individually and in the mixture and F400 showed higher sorption capacity than CBC. The presence of co‐contaminants (kerosene, trichloroethylene, and ethanol), and variations in groundwater conditions (pH, presence of SO 4 − 2 anions, naturally occurring organic matter, and iron oxides) demonstrated limited impact on the sorption of PFAS onto GAC under the experimental conditions tested.